Factors Precipitating Hypokalemia in Diabetic Patients: A Cross Sectional Study (Journal of Enam Medical College, 2014)
Background: Hypokalemia is a very common electrolyte imbalance in diabetic patients which leads to substantial morbidity and mortality. Severe hypokalemia is associated with lifethreatening arrhythmias and sudden cardiac death. There are no adequate studies regarding the incidence and factors precipitating hypokalemia in Bangladeshi diabetic subjects. Objective: The objective of this study was to find out the factors precipitaing hypokalemia in diabetic patients. Materials and Methods: A total 95 admitted diabetic patients with hypokalemia were studied. Specimens were collected from all adult diabetic patients with serum potassium level